Influence of different boron precursors on superconducting and mechanical properties of MgB2 - Safran, S.; Kılıç, A.; Asikuzun, E.; Kılıçarslan, E.; Ozturk, O.; Gencer, A. (Springer Science and Business Media LLC, 2014)
The superconducting, structural and mechanical properties of MgB2 bulk samples have been studied as a function of precursor B powder particle size by means of AC susceptibility, XRD and microhardness measurements, respectively. The in situ processed MgB2 samples have been prepared by means of conventional solid state reaction method with magnesium powder (99.8 %, 325 mesh) and four different types of boron powders (95.2, >95, 91.9 and 86.7 %) from two sources, Pavezyum and Sigma Aldrich. The XRD measurements showed that the diffraction peaks for our samples belong to the main phase of the MgB2 diffraction patterns. The highest critical temperature T c = 37.7 K was achieved for the MgB2 sample which was fabricated by using >95 % purity amorphous boron. Microhardness measurements were performed to investigate the mechanical properties. Load independent hardness, Vickers microhardness, Young’s modulus, fracture toughness, and yield strength values were calculated separately for all samples. The results were analyzed by using the Meyer’s law, proportional sample resistance model, elastic–plastic deformation model, Hays Kendall approach, and indentation induced cracking (IIC) model. It was found that the IIC model is the most successful model to describe the mechanical properties of our samples.